EFFECT OF ATROPINE EYE DROPS 0.01% ON MYOPIA PROGRESSION IN HIGH AND LOW MYOPIA IN PATIENTS VISITING ARMED FORCES INSTITUTE OF OPHTHALMOLO - Ashraf, Ammarah; Masud, Hannan; Basit, Imran; Awan, Muhammad Manzoor (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the effect of atropine eye drop 0.01% on myopia progression in high and low myopes.Study Design: Quasi experimental study.Place and Duration of study: Armed Forces Institute of Ophthalmology (AFIO) Rawalpindi, Pakistan from Mar 2017 to Jul 2018.Methodology: A total of 72 eyes of 36 patients successfully completed the follow up. Age ranging from 5 to 15 years, refractive error from 2.0D to 20D was considered and grouped into high and low myope on the basis of refractive error and axial length (AL). Those with other ocular disease were excluded. Increase in Axial Lenght of 0.5mm or refractive error 0.5D in 3 months were started 0.01% atropine eye drop in both eyes. Follow up was 3 monthly, final readings of axial length and spherical equivalent (SE) were noted at 12 months of treatment initiation.Results: The mean spherical equivalent and axial length in group high myopes was 12.40D ± 3.55 and 27.28 ± 1.19mm respectively while in group low myopes was 4.99D ± 0.68 and 24.27 ± 1.40 mm respectively. The induced change in spherical equivalent and axial length at the end of 01 year after atropine treatment was 0.81 ± 0.26 D and 0.77 ± 0.16 mm respectively in group high myopes while 0.76 ± 0.21 D and 0.81 ± 0.26 mm respectively in group LM. There was statistically no significant difference of induced change between the two groups.Conclusion: Atropine eye drop (0.01%) was effective in halting myopia progression in both high and low myopes.